Tren Penelitian Biofilik: Sebuah Tinjauan Literatur dengan Analisis Bibliometrik - Ratnasari, Anisza; Basuki Dwisusanto, Yohanes (Prodi Arsitektur Universitas Matana, 2024)
Biophilic design is a design approach that integrates natural elements into the built environment. Biophilic research has rapidly expanded into design, health, psychology, and technology. This study aims to explore trends of biophilic research, identify the relationships between scientific concepts, and reveal opportunities for further research. This library-based study employs a literature review method using bibliometric analysis. Digital data collection was obtained through Google Scholar for 2004-2024 with keywords 'biophilic', 'biophilic design', 'nature connection', and 'biophilia hypothesis'. Meta-data collection was conducted using Publish or Perish (PoP). Subsequently, VOSviewer was employed to create scientific maps for bibliometric analysis, and lens.org was utilized to conduct performance analysis. The findings reveal that over the past two decades, the number of publications on biophilic research in scientific journals has grown across various academic disciplines. Keyword-based mapping indicates the existence of conceptual relationships in psychology, environment, architecture, and ecology with six dominant clusters, namely; 'biophilic design strategy', 'biophilic urbanism', 'biophilic design framework', 'wellness and mental health', 'healing', and 'biophilic elements'. Based on these results, there are significant opportunities for further biophilic research in architecture and psychology scope, focusing on the design of built environments that incorporate natural elements into the built environment.